AUDIT DELAY, PROFITABILITY, DAN KONTRIBUSINYA TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN - Dewi Rahmayanti (STIE AUB Surakarta, 2016)
This study intents to investigate the influence of audit delay and profitability, towards the financial reporting timeliness in Indonesia stock exchange. Specifically, the sample in this research is obtained from 75 public listed companies (PLC) of manufacturing sector, in Indonesia Stock Exchange. The time period of study is ranging from 2009 to 2011. Further, hypotheses testing were conducted by employing Pooled Least Squared (PLS) Model with panel data analysis. The output performed that audit delay was significantly (p